Power supply devices and systems of relay protection - Gurevich, Vladimir 1956- (CRC Press, 2014)
This book describes the arrangement, mode of action and problems of secondary power supplies of digital protective relays, stationary accumulator batteries, battery chargers, uninterruptible power supplies and auxiliary AC and DC power supply systems of substation and power plants. It reviews the issues of insulation monitoring in DC systems, the problems of monitoring the integrity of substation battery circuit, problems of voltage dips and how to address them as well as a number of other questions that arise in the course of the exploitation of auxiliary power systems and the on-site needs of substations and power plants